Digital Marketing Communication Patterns for Islamic Microfinance Institutions in the Industrial Era 4.0 - Riduan Mas’ud (UIN Sunan Gunung Djati, 2021)
This study tries to show that implementing a comprehensive marketing program will help Islamic microfinance institutions (LKMS) improve their overall performance, especially in the current industrial era. Like other Islamic organizations, Islamic microfinance institutions must follow Islamic (Sharia) rules in all aspects of a business. Then a marketing program suitable for Islamic microfinance institutions must include a marketing concept established by relying on Islamic values. Similar to other organizations, the main objective of the marketing program of Islamic microfinance institutions is to retain existing customers and attract new customers. In addition, an efficient marketing program must contain several specifications emphasizing the nature of the market and the institution itself, competitors, development of marketing plans, and client preferences. Some concrete steps that need to be taken by LKMS are using Internet of Things (IoT) technology, cloud computing, big data and customer profiling, and electronic payments